Synthesis of organic-inorganic hybrid nanocomposite material: toluene-4-sulfonate in the lamella of zinc-aluminium-layered double hydroxide - Hussein, Mohd. Zobir; Lim, Sheau Wen; Yahaya, Asmah; Zainal, Zulkarnain (Universiti Putra Malaysia Press, 2005)
Open lamella systems such as layered double hydroxides (LDHs) can be used to generate new nanostructured materials of layered organic-inorganic nanohybrid type. The inorganic Zn-Al-layered double hydroxide (ZAL) was used as matrix, hosting an active agent or guest, toluene-4-sulfonate (TSA). They were prepared by spontaneous selfassembly method from an aqueous solution for the formation of a new layered organicinorganic hybrid nanocomposite material (ZALTSA). In this synthesis, the host and the guest forming species were simultaneously included in the mother liquor, aged and separated. In this study, the Zn/Al ratio at R=4, concentrations of TSA (0.10-0.40 M) and pH 7 and pH 10 were used to optimize the formation of the layered nanocomposite. The concentration of TSA of 0.40 M at pH 10 was found to be able to give well-ordered nanolayered organic-inorganic hybrid structure. PXRD and FTIR analyses showed that the organic-inorganic structure of LDH expanded from 8.8 Å to 17.3 Å to accommodate the TSA for the formation of the nanocomposite. The BET surface area of the resulting ZAL and its nanocomposite ZALTSA are 9 m2/g and 5 m2/g, respectively. No significant difference in the surface morphology of ZAL and ZALTSA was observed under a scanning electron microscope. Both of them afforded non-uniform irregular agglomerates of compact and non-porous structure of plate-like morphology.